THE ECONOMIC AND FINANCIAL PERFORMANCE OF TOUR OPERATORS IN ITALY, FRANCE AND SPAIN: SOME COMPARATIVE EVIDENCE - Guido Migliaccio; Maria Calvanese (Economy and Sociology)
Purpose. This article describes and evaluates the economic and financial dynamics of tour operators over the last decade in Italy, France and Spain, three European countries where tourism is relevant.